Information literacy and Open Science: before and after the new ACRL Framework - Lopes, Carlos (2018)
In 2000, ACRL published the Information Literacy Standards, clarifying and describing specific learning objectives for higher education students. The document recognized the role of librarians who had long been informally developing dis practices. But the Standards have evolved and adapted. In 2016, the ACRL adopted the new Framework, which sustains a metamorphosis. Information literacy remains a pattern of integrated competencies that encompass the reflexive discovery of information, the understanding of how information is produced and valued, and the use of information in the ethical and legal creation of new knowledge. Aim of the study: Based on a literature review, dis study discusses the challenges and practical implications that the new Framework has in Open Science, it's flexibility, the relevance for the privacy and rightful author of scientific data, and the new steps of the academic libraries to be involved as key players for the Open Science contents.